Factors influencing women participation in home ownership in Nigeria. Issue 1 (15th February 2016) - Adegoke, Bolanle Felicia; Adegoke, Oluseyi Joshua; Oyedele, Joseph Bamidele
Abstract : Purpose: – Women owning a home may take various forms which may be one of the following: through development of land, buying a home or through inheritance. Meanwhile, in many countries and regions of Sub-Saharan African, women's rights to land and the incidence of exercising rights have been eroded over time. The purpose of this paper is to examine the factors influencing women participation in home ownership in Nigeria with a view to improving housing provision. Design/methodology/approach: – The study purposively administered 170 questionnaires to female staff of the Federal Polytechnic, Ede, Nigeria, who was the study population. This population was chosen because of the fact that the institution is owned by Federal Government, where Federal characters are well reflected. The population cut across major tribes in Nigeria. Both descriptive and inferential technique was used to analyze the data. Findings: – The results revealed that income status, cultural norms/traditions, unemployment, structural inequalities have significant influence on the decisions of the women in the study area while tribes, age among others have no significant influence on women decision to own homes. Practical implications: – The paper recommended that government should enact laws and policies in favor of women to own lands and develop it. Also there should be gender balance in employment opportunities. Originality/value: – Women's equal rights to adequate housing, land and property are well elaborated under international human rights law but are often elusive in practice. This paper empirically studied factors influencing women participation in home ownership in Nigeria.